2021
DOI: 10.3389/fonc.2021.614211
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of a Prognostic Gene Signature for Diffuse Large B-Cell Lymphoma Based on Tumor Microenvironment-Related Genes

Abstract: Diffuse large B-cell lymphoma (DLBCL) is an extremely heterogeneous tumor entity, which makes prognostic prediction challenging. The tumor microenvironment (TME) has a crucial role in fostering and restraining tumor development. Consequently, we performed a systematic investigation of the TME and genetic factors associated with DLBCL to identify prognostic biomarkers for DLBCL. Data for a total of 1,084 DLBCL patients from the Gene Expression Omnibus database were included in this study, and patients were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Few studies have given emphasis on extracellular matrix, an important part of tumor microenvironment. Recently, a group identified a genetic signature based on TME-related genes, comprising TIMP2, QKI, LCP2, LAMP2, ITGAM, CSF3R, and AAK1 [40], by calculating the abundance of immune-stromal components, and from this group they further obtained differentially expressed genes. In our research, we found that extracellular matrix structural constituents such as the networkforming collagen trimer and collagen type IV trimer were upregulated in the Sub-DLBCL group, which may contribute to the development of DLBCL located under diaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have given emphasis on extracellular matrix, an important part of tumor microenvironment. Recently, a group identified a genetic signature based on TME-related genes, comprising TIMP2, QKI, LCP2, LAMP2, ITGAM, CSF3R, and AAK1 [40], by calculating the abundance of immune-stromal components, and from this group they further obtained differentially expressed genes. In our research, we found that extracellular matrix structural constituents such as the networkforming collagen trimer and collagen type IV trimer were upregulated in the Sub-DLBCL group, which may contribute to the development of DLBCL located under diaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…In the similar study published in 2021, Pan et al 49 established a tumor microenvironment (TME) related prognostic signature for DLBCL patients. When combining with IPI components, it is a promising prognostic model not only to help clarifying immune responses in the DLBCL microenvironment but also to indicate new clinical applications for immune therapy and individualized therapy in patients with DLBCL.…”
Section: Discussionmentioning
confidence: 96%
“…As the data source, SEER, did not provide the IPI scores of the patients, we cannot compare this nomogram with the IPI scoring system. In addition, the results of this study ignored the genetic characteristics, which are now proved to be important in the diagnosis and prognosis of the disease [ 21 , 22 ]. Even so, our study remains an instructive and efficient model of PG-DLBCL prognosis.…”
Section: Discussionmentioning
confidence: 99%